New and additional records of Anacroneuria Klapálek (Plecoptera: Insecta) from Tocantins state, Brazil - Rippel, Mellis Layra Soares; Salles, Frederico Falcão; Fernandes, André Silva; Krolow, Tiago Kütter (Zootaxa, 2023)
In this study we provide an updated list of Plecoptera based on recent collections covering areas from northern to southeastern Tocantins state, Brazil. It is the first work focused on the geographical distribution of the order in this region. Herein, we register Anacroneuria atrifrons Klapálek, 1922, Anacroneuria jaciara Bispo & Neves, 2005, Anacroneuria manauensis Ribeiro-Ferreira, 2001, and Anacroneuria terere Righi-Cavallaro & Lecci, 2010 for the first time to Tocantins with notes and illustrations of diagnostic features for these four species. Our work raises the number of stoneflies known from Tocantins to 13 species. Despite this increase in the number of species, we highlight the importance of expanding field collection efforts in different locations of the state, especially in the west and south regions, as well as increasing collection effort in each location, aiming for a better comprehension of this fauna.